Preparation and Characterization of Auricularia cornea Ehrenb Polysaccharide-Zn Complex and Its Hypoglycemic Activity through Regulating Insulin Resistance in HepG2 Cells - Tingting Liu; Shanshan Zhang; Nan Wang; Xinle Xu; Hongcheng Liu; Dawei Wang; Yanrong Zhang (Journal of Food Quality)
With Auricularia cornea Ehrenb polysaccharide (ACEP) as raw material, the purpose of the study was to prepare Auricularia cornea Ehrenb polysaccharide-zinc (ACEP-Zn) complex. Fourier transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD), scanning electron microscopy (SEM), nuclear magnetic resonance (NMR), and other means are used to analyze the physical-chemical properties and structure of ACEP and ACEP-Zn, to investigate the inhibition of α-glycosidase and α-amylase enzymes, and to explore its effects on the glucose metabolism of insulin-resistant HepG2 cells. Nuclear magnetic resonance (NMR) results show that a group of COO-, -CH3, and -OH in the sugar chain binds to Zn2+. Compared with the original polysaccharides, the surface morphology of ACEP-Zn changed obviously, and the molecular weight (Mn) of ACEP-Zn decreased, but the molecular agglomeration of ACEP-Zn increased. Moreover, the inhibitory effect of ACEP-Zn on α-glucosidase and α-amylase was stronger than that of the original polysaccharide. The results indicated that the structure of Auricularia cornea Ehrenb polysaccharide was changed obviously after the zinc complex, and its hypoglycemic activity was enhanced in vitro. In the cell experiment, the glucose consumption of IR-HepG2 cells was significantly increased at a concentration of 50–200 μg/mL (P<0.05). The activity of SOD and NOS significantly increased (P<0.01), and the activity of intracellular PK increased (P<0.05). Therefore, it was speculated that the hypoglycemic effect of Auricularia cornea Ehrenb polysaccharide combined with zinc was related to the alleviation of liver cell damage caused by oxidative stress and the improvement of glucose metabolism of IR-HepG2 cells. The study provides a theoretical basis for the application of the polysaccharide-zinc complex in the hypoglycemic functional food field.